Comparison of Reoperation after Fusion and after Decompression for Degenerative Lumbar Spinal Stenosis: A Single-Center Experience of 987 Cases - Kim, Seung-Kook; Park, Seoung-woo; Lim, Byun-chul; Lee, Su-Chan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Study Aim Reoperation for lumbar spinal stenosis (LSS) is technically challenging. Studies comparing preoperative risk factors and reoperation outcomes between spinal fusion and spinal decompression are limited. Thus this study compared fusion and decompression with respect to reoperation rates, preoperative factors related to re-surgery, and clinical outcomes.Patients and Methods This retrospective cohort study included prospectively collected data from patients who underwent revision surgeries for degenerative LSS between May 2001 and March 2015. The reoperation rate, risk factors (proportional hazards analysis of index surgery), surgery type, main reason for revision, and final clinical outcomes (pain, quality-of-life modification, patient satisfaction, and complication rate) were analyzed and compared between the fusion and decompression surgeries.Results Among 987 cases during 13 years, 25 cases of reoperation after fusion and 23 cases of reoperation after decompression were identified, accounting for reoperation rates of 5.88% and 4.00%, respectively. Combined comorbidities (hazard ratio [HR]: 1.98 for fusion; multilevel involvement [with fusion, HR: 2.92; decompression, HR: 1.95]) were strongly correlated with preoperative demographic risk factor for each procedure. The main reason for reoperation in fusion cases was proximal junctional kyphosis (40%) and implant failure (20%), and in decompression cases, recurrent lesions (48.8%) and incomplete surgery (17.4%) An additional fusion after initial fusion and re-decompression without fusion after initial decompression were the most common surgical procedure. Back pain and patient satisfaction after fusion were better compared with those after decompression.Conclusion The reoperation rate, preoperative risk factors, reason for revision, reoperation type, clinical outcomes, patient satisfaction, and time interval between index and re-surgery were different between the primary fusion and primary decompression. A better understanding of disease pathophysiology and surgical procedure characteristics will facilitate improvement in disease management and the development of treatment strategies.
Keywords: revision surgery; reoperation; microscopic spinal decompression; proximal junctional kyphosis